Penguatan Karakter Santri sebagai Strategi Menghadapi Tantangan Globalisasi di Pesantren Darussalam Blokagung - Ahmad Reza Maulana; Salsabila Wulandari; Rezza Mifachu Rizqi; Tajriyah Tajriyah; Arlino Pratama; Mochammad Faisal Mulyawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to describe the strategy of strengthening the character of santri in facing the challenges of globalization at the Darussalam Blokagung Islamic Boarding School. Using a descriptive qualitative approach, this study reveals that the integration of Islamic values in the formal and informal learning system of pesantren plays a significant role in shaping the resilient and adaptive character of santri. The process of character education does not only take place through teaching materials, but also through the example of ustadz, family involvement, and a collective pesantren culture. The pesantren combines salaf and khalaf education to produce religious, independent, and globally competitive santri. Adaptive strategies such as strengthening foreign languages, vocational training, and controlling the use of technology are proof of the readiness of pesantren to face the digital era. This research recommends the development of an integrated and contextual character education system so that moral values are preserved amid the increasingly strong globalization.